Extracts of Talaromyces purpureogenus Strains from Apis mellifera Bee Bread Inhibit the Growth of Paenibacillus spp. In Vitro - Vocadlova, Katerina; Lüddecke, Tim; Patras, Maria A; Marner, Michael; Hartwig, Christoph; Benes, Karel; Matha, Vladimir; Mraz, Petr; Schäberle, Till F; Vilcinskas, Andreas (Microorganisms, 2023)
Honey bees coexist with fungi that colonize hive surfaces and pollen. Some of these fungi are opportunistic pathogens, but many are beneficial species that produce antimicrobial compounds for pollen conservation and the regulation of pathogen populations. In this study, we tested the in vitro antimicrobial activity of Talaromyces purpureogenus strains isolated from bee bread against Paenibacillus alvei (associated with European foulbrood disease) and three Aspergillus species that cause stonebrood disease. We found that methanol extracts of T. purpureogenus strains B18 and B195 inhibited the growth of P. alvei at a concentration of 0.39 mg/mL. Bioactivity-guided dereplication revealed that the activity of the crude extracts correlated with the presence of diketopiperazines, a siderophore, and three unknown compounds. We propose that non-pathogenic fungi such as Talaromyces spp. and their metabolites in bee bread could be an important requirement to prevent disease. Agricultural practices involving the use of fungicides can disrupt the fungal community and thus negatively affect the health of bee colonies.
Keywords: Apis mellifera; fungi; antimicrobial activity; biocontrol; honey bee; bee bread; natural product; Talaromyces